Дијалектолошката перспектива на микротопонимијата претставена преку материјал од Крушевскиот регион (во Република Македонија) - Момировска, Мери (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
Main topic of this article is the link between dialectology and local microtoponymy. Microtoponyms are unofficial forms that are not recorded in administrative documents. They have only limited use in local comunities. So they reflect dilectal features of vernacular. The toponyms from Krushevo region contain all features of Krushevo dialect, as: the phonetic, phnological, morphological, lexical and the sintactical one.